Knowledge Management and World ClassManufacturing: an initial approach based on a literature review (Perspectivas em Ciência da Informação, 2017)
This paper represents the partial results of an ongoing research on the proposal of a methodology for the integration between Knowledge Management (KM) and World Class Manufacturing (WCM), and presents the results of an initial investigation of theoretical and conceptual nature aimed at developing a comprehensive and current vision on KM, WCM, and how (or "whether") these constructs relate to one another. The primary sources used were Web of Science, Scopus, Emerald, Ebsco, SciELO and Spell, consulted for the period from 2000 to 2016. The analysis of the selected papers showed that, although the initial WCM model evolved into a "new WCM" in the 2000s, the literature is still focused on the broad conceptual aspects and basic methods and tools, such as Total Quality Process, Total Productive Maintenance and Just-in-Time, conceived in the Toyota Production System, which shows the need for more studies focused on the current scenario of companies associated with the "new WCM" and its Methods and Tools. Only one article explicitly addressing the interaction between KM theories with WCM was found in the databases surveyed, thus reinforcing the lack of theoretical approximation of these constructs.